Web 2.0 Era - An innovative andragogy to empower students through Social Networking Sites - Chauhan, Meenal; Mundi, Navreet Kaur (Gyan Management Journal, 2011)
Web 2.0 has the power to impact teaching and learning in ways that engage today's students in an interesting and relevant use of technology tools and resources while building social networks that inform and connect. This paper examines the role of technology in shaping the future of higher education using the social network sites, like Or/wt, Facebook, You Tube etc. that can support these activities. The study would help the academicians to use SNS in improving their teaching andragogy for higher Education.
Keywords: Social Networking; Web2.0; Facebook; Andragogy